Integrative focus on the space exposome-integrome: physiological challenges and practical limits of countermeasures beyond low Earth orbit - Bailey, Damian M.; Blottner, Dieter; Gunga, Hanns Christian; Schneider, Stefan; Wotring, Virginia; Baatout, Sarah; Durante, Marco; Olde Engberink, Rik H.G.; Goswami, Nandu; Heer, Martina; Liphardt, Anna-Maria; Monici, Monica; et al. (npj microgravity, 2025)
Human spaceflight is advancing toward sustainable exploration through initiatives like NASA’s Artemis program, aiming for a lunar outpost and eventual Mars mission. Astronauts face hazards including altered gravity, isolation, and cosmic radiation, linked to over thirty health risks. This review, reflecting ESA community expertise, outlines how understanding the space exposome–integrome interaction can improve risk stratification, guide personalized countermeasures, and address knowledge gaps essential for safe deep-space exploration.
CRIS-Team Scopus Importer:2025-12-05